PRODUCCIÓN DE BIOGÁS EN UN PROTOTIPO DE BIODIGESTOR A CONDICIONES AMBIENTALES DE HUANCAVELICA - Huere Peña, Jorge Luis (2015)
Objective: To determine technical parameters to design a biodigester prototype in Huancavelica ́s environmental conditions favorable for optimal and efficient production of methane gas (CH4). Methods: The methodology used is based on the design and construction of an anaerobic biodigester laboratory (prototype), as well as its implementation and practical application through testing, in which biogas production to different environmental conditions was analyzed to determine the influence of temperature on the quality and quantity of produced biogas besides their influence on other parameters. It has been made a program of four experiments where there have been controlled parameters such as temperature, pH, and COD (Chemical Oxygen Demand). Results: The biodigester average temperature was 33°C due to heating from outside through a greenhouse, a standard deviation of 1,41, and temperature fluctuations during that period were from 31°C to 37°C. An average inside pH of the biodigester of 6,89, with a standard deviation of 0,23, and the pH variations ranged from 6,5 to 7,3; the methane content (CH4) obtained was 56 mol% and CO2 content was 34% mol achieving an acceptable biogas. Conclusions: A limitation in this study was the climatic type, being a good alternative the implementation of greenhouses achieving mesophilic temperatures, with a daily production of biogas approximately of 0, 2 m3biogas/m3digester/day. The more efficient mixture percentage in mesophilic conditions was the corresponding to mixture containing 25% v/v of bovine manure and 75% v/v of water and mechanical agitation incorporation, obtaining 62% and 75,7% of COD removal and with a start time of 22 days approximately.